Mice with an N-Ethyl-N-Nitrosourea (ENU) Induced Tyr209Asn Mutation in Natriuretic Peptide Receptor 3 (NPR3) Provide a Model for Kyphosis Associated with Activation of the MAPK Signaling Pathway. - Christopher T Esapa; Sian E Piret; M Andrew Nesbit; Nellie Y Loh; Gethin Thomas; Peter I Croucher; Matthew A Brown; Steve D M Brown; Roger D Cox; Rajesh V Thakker (PLoS ONE)
Non-syndromic kyphosis is a common disorder that is associated with significant morbidity and has a strong genetic involvement; however, the causative genes remain to be identified, as such studies are hampered by genetic heterogeneity, small families and various modes of inheritance. To overcome these limitations, we investigated 12 week old progeny of mice treated with the chemical mutagen N-ethyl-N-nitrosourea (ENU) using phenotypic assessments including dysmorphology, radiography, and dual-energy X-ray absorptiometry. This identified a mouse with autosomal recessive kyphosis (KYLB). KYLB mice, when compared to unaffected littermates, had: thoraco-lumbar kyphosis, larger vertebrae, and increased body length and increased bone area. In addition, female KYLB mice had increases in bone mineral content and plasma alkaline phosphatase activity. Recombination mapping localized the Kylb locus to a 5.5Mb region on chromosome 15A1, which contained 51 genes, including the natriuretic peptide receptor 3 (Npr3) gene. DNA sequence analysis of Npr3 identified a missense mutation, Tyr209Asn, which introduced an N-linked glycosylation consensus sequence. Expression of wild-type NPR3 and the KYLB-associated Tyr209Asn NPR3 mutant in COS-7 cells demonstrated the mutant to be associated with abnormal N-linked glycosylation and retention in the endoplasmic reticulum that resulted in its absence from the plasma membrane. NPR3 is a decoy receptor for C-type natriuretic peptide (CNP), which also binds to NPR2 and stimulates mitogen-activated protein kinase (MAPK) signaling, thereby increasing the number and size of hypertrophic chondrocytes. Histomorphometric analysis of KYLB vertebrae and tibiae showed delayed endochondral ossification and expansion of the hypertrophic zones of the growth plates, and immunohistochemistry revealed increased p38 MAPK phosphorylation throughout the growth plates of KYLB vertebrae. Thus, we established a model of kyphosis due to a novel NPR3 mutation, in which loss of plasma membrane NPR3 expression results in increased MAPK pathway activation, causing elongation of the vertebrae and resulting in kyphosis.